The role of hotels in responding to pandemics: a case study of Covid-19 and hotels in Cape Town, South Africa - Beneke, Neno Amurie (Stellenbosch : Stellenbosch University, 2024)
Thesis (MPhil)--Stellenbosch University, 2024.